2021
DOI: 10.1111/bjh.17232
|View full text |Cite|
|
Sign up to set email alerts
|

Eltrombopag added to immunosuppression for children with treatment‐naïve severe aplastic anaemia

Abstract: Acquired severe aplastic anaemia (SAA) has an immune pathogenesis, and immunosuppressive therapy (IST) with anti-thymocyte globulin and cyclosporine is effective therapy. Eltrombopag (EPAG) added to standard IST was associated with higher overall and complete response rates in patients with treatment-na€ ıve SAA compared to a historical IST cohort. We performed a paediatric subgroup analysis of this trial including all patients aged <18 years who received EPAG plus standard IST (n = 40 patients) compared to a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(43 citation statements)
references
References 30 publications
(51 reference statements)
0
34
0
Order By: Relevance
“…Notably, the overall response rate (complete and partial response) at month 6 in cohort 3 was 80%, which was significantly higher than the 66% overall response rate observed in a historical cohort of 102 patients with SAA who received antithymocyte globulin and cyclosporine alone [71]. Although eltrombopag is approved for use in combination with standard immunosuppressive therapy in adults and children aged 2 years and older with severe aplastic anemia, a recent subgroup analysis of 40 pediatric patients receiving eltrombopag plus immunosuppressive therapy versus a historical cohort of 87 children receiving immunosuppressive therapy alone did not identify a significant improvement in overall response rates (70% with eltrombopag plus immunosuppressive therapy versus 72% in the historical cohort of children receiving immunosuppressive therapy alone; p = 0.78) [30,72].…”
Section: Severe Aplastic Anemiamentioning
confidence: 99%
“…Notably, the overall response rate (complete and partial response) at month 6 in cohort 3 was 80%, which was significantly higher than the 66% overall response rate observed in a historical cohort of 102 patients with SAA who received antithymocyte globulin and cyclosporine alone [71]. Although eltrombopag is approved for use in combination with standard immunosuppressive therapy in adults and children aged 2 years and older with severe aplastic anemia, a recent subgroup analysis of 40 pediatric patients receiving eltrombopag plus immunosuppressive therapy versus a historical cohort of 87 children receiving immunosuppressive therapy alone did not identify a significant improvement in overall response rates (70% with eltrombopag plus immunosuppressive therapy versus 72% in the historical cohort of children receiving immunosuppressive therapy alone; p = 0.78) [30,72].…”
Section: Severe Aplastic Anemiamentioning
confidence: 99%
“…A subgroup analysis of 40 patients <18 years of age who received ACE was compared to a historical cohort (n = 87) of paediatric patients treated with IST only. 218 The overall haematologic response rate was 70% in the eltrombopag group, which did not differ from that in the comparator cohort (72%; P = 0Á78). Relapses and clonal evolution rates occurred at similar rates in the ACE and historical groups.…”
Section: Some Questions Remainmentioning
confidence: 81%
“…A smaller proportion of patients in the NIH ACE study was children. A subgroup analysis of 40 patients <18 years of age who received ACE was compared to a historical cohort ( n = 87) of paediatric patients treated with IST only 218 . The overall haematologic response rate was 70% in the eltrombopag group, which did not differ from that in the comparator cohort (72%; P = 0·78).…”
Section: Therapymentioning
confidence: 99%
“…Our results show that a median time to transplantation of 4.5 months leaves a window of opportunity for a nontransplant strategy before the availability of the alternative donor. The chance of improving IS results can be seen in using new drugs, such as thrombopoietin receptor antagonists, which have been shown to stimulate the proliferation of autologous hematopoietic stem cells, resulting in the licensing of eltrombopag in SAA in adults and children over 12 years of age, but studies in children have not confirmed the efficacy of SAA upfront therapy [ 58 , 59 ].…”
Section: Discussionmentioning
confidence: 99%